Fragile Masculinity in Eka Kurniawan Novel Anjing Mengeong Kucing Menggonggong: Raewyn Conell’s Hegemony of Masculinity - Esty Pratiwi Lubarman; Intan Fajriyah; Asy'ari , Farosya (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Eka Kurniawan's novel titled Anjing Mengeong Kucing Menggonggong (2024) tells the story of a boy named Sato Reang who was born into a conservative family. He was educated with strong religious morals, especially his father who taught him a lot to obey religious rules. In his growth and development, he always wanted to be free from religious doctrines that curbed his freedom as a boy. This conflict began, when he had to perform the circumcision tradition as a sign that he was an adult. And forced him to submit to religious morals, which had been going on for generations in his family. He wanted freedom as a boy, until one day his father died and he didn't have to pray, recite or even go to school. However, the shadow of his father always haunts him, every action and interaction with society he always remembers his father's commandments. There is a relationship between masculinity and piety in the novel, which shows how the conception of gender works within a particular cultural concept and context. The piety inherited by a father makes dominance over the figure of the son in the family structure and society. Using the Raewyn Connell approach, this study will explore the interaction of masculinity and piety as a construction that oppresses the dominant gender itself. This research will use a qualitative descriptive method. The formulation of the problem in this study is, 1) How does obedience in religious practice shape the masculinity of the main character Sato Reang? 2) How is the representation of fragile masculinity as a criticism of the hegemony of masculinity portrayed by Eka Kurniawan? The result of this research is to answer the individual's adherence to religious practices that form the fragile masculinity of Sato Reang, then show this novel as an effort to criticize Eka Kurniawan as a writer against the hegemony of masculinity that he does to the character of Sato Reang based on the social reality presented in the novel.